Modulation of a rapid neurotransmitter receptor-ion channel by membrane lipids - Barrantes, Francisco Jose (2024)
Membrane lipids modulate the proteins embedded in the bilayer matrix by two non-exclusive mechanisms: direct or indirect. The latter comprise those effects mediated by the physicochemical state of the membrane bilayer, whereas direct modulation entails the more specific regulatory effects transduced via recognition sites on the target membrane protein. The nicotinic acetylcholine receptor (nAChR), the paradigm member of the pentameric ligand-gated ion channel (pLGIC) superfamily of rapid neurotransmitter receptors, is modulated by both mechanisms. Reciprocally, the nAChR protein exerts influence on its surrounding interstitial lipids. Folding, conformational equilibria, ligand binding,ion permeation, topography, and diffusion of the nAChR are modulated by membrane lipids. The knowledge gained from biophysical studies of this prototypic membrane protein can be applied to other neurotransmitter receptors and most other integral membrane proteins.